0
$\begingroup$

"Let $\hat{ABC}$ be an isosceles triangle with $AB=AC$. $D$ is a point on $BC$ such that $DC=DB$ (middle of $BC$). $E$ is the projection of $D$ on $AC$ and $F$ the middle of $DE$. Prove, using vectors that $AF$ and $BE$ are perpendicular."

The start should be that $AF$ and $BE$ are perpendiculars $\iff$ the scalar product of $AF$ and $BE = 0$. Any nice solution using vector geometry? A synthetic one or with complex numbers would be appreciated as well!

$\endgroup$
  • $\begingroup$ "DA=DB" does not mean "middle of BC" $\endgroup$ – sds Jun 11 '14 at 16:53
  • $\begingroup$ It was a mistake! It must be DB=DC. $\endgroup$ – user146371 Jun 11 '14 at 16:58
0
$\begingroup$

Let $A$ be your origin, $\vec b=AB$, $\vec c=AC$. Then

  1. Express the isosceles condition in terms of $\vec b$ and $\vec c$.
  2. Express vector $AD$ in terms of $\vec b$ and $\vec c$.
  3. Likewise for vector $AE$
  4. Likewise for vector $AF$
  5. Likewise for vector $BE$
  6. Scalar multiply the results from 4 & 5 and use 1 to get 0.
$\endgroup$
0
$\begingroup$

Let's express almost all the vectors as relative to point $D$: $$ \begin{array}{ccccc} \vec{a} \equiv \vec{DA} & & \vec{c} \equiv \vec{DC} & & \vec{b} \equiv \vec{DC} = -\vec{c}\\ \vec{e} \equiv \vec{DE} & & \vec{f} \equiv \vec{DF} = \frac{1}{2} \vec{e} & &\vec{g} \equiv \vec{AC} = \vec{c}\vec{a} \end{array} $$ Then since $\triangle BAC$ is isosceles, $AD$ is an altitude, hence $$ \begin{array}{c} \vec{c} \cdot \vec{a} = 0 \\ \vec{c} \cdot \vec{g} = \vec{c} \cdot \vec{g} = \vec{c} \cdot \vec{c} - \vec{c} \cdot \vec{a} = |c|^2 \end{array} $$ Point $E$ is on line $AC$ so for some real $\kappa$ $$ \vec{e} = \vec{c} + \kappa (\vec{c} - \vec{a}) = \vec{c} + \kappa \vec{g} $$ We now enforce the fact that $DE \perp AC$ by $$ \begin{array}{l} \vec{e} \cdot \vec{g} = 0 \\ (\vec{c} + \kappa \vec{g}) \cdot \vec{g} = 0 \\ \vec{c} \cdot \vec{g} + \kappa |g|^2 = 0 \\ \kappa = -\frac{\vec{c} \cdot \vec{g}}{g^2} = -\frac{c^2}{g^2}\\ \vec{e} = \vec{c} - \frac{c^2}{g^2} \vec{g} \end{array} $$ And $\vec{f} = \frac{1}{2}\vec{e}$. Now we express $AF$ and $BE$ $$ \begin{array}{l} \vec{AF} = \vec{f} - \vec{a} = \vec{f} - \vec{c} + \vec{g} \\ 2 g^2 \vec{AF} = g^2 \vec{c} - c^2 \vec{g} - 2 g^2 \vec{c} + 2 g^2 \vec{g} \\ 2 g^2 \vec{AF} = - g^2 \vec{c} - c^2 \vec{g} + g^2 \vec{c} \\ \vec{BE} = \vec{e} - \vec{b} = \vec{e} + \vec{c} \\ g^2 \vec{BE} = 2 g^2 \vec{c} - c^2 \vec{g} \end{array} $$ Finally, we examine the dot product. Since $|g|$ is the positive length of $AC$, if the dot product of $2 g^2 \vec{AF}$ and $g^2 \vec{BE}$ is zero, that will prove that $AF \perp BE$. $$ \begin{array}{l} 4 g^4 \vec{BE} \cdot \vec{AF} = \left( 2 g^2 \vec{c} - c^2 \vec{g} \right) \cdot \left( 2 g^2 \vec{g} - g^2 \vec{c} - c^2 \vec{g} \right) \\ = 4 g^4 \vec{c} \cdot \vec{g} -2 g^4 c^2 - 2 g^2 c^2 \vec{c} \cdot \vec{g} - 2 g^4 c^2 + c^2 g^2 \vec{c} \cdot \vec{g} + g^2 c^4 \\ = 4 g^4 c^2 -2 g^4 c^2 - 2 g^2 c^4 - 2 g^4 c^2 + c^2 g^2 c^2 + g^2 c^4 =0 \end{array} $$

$\endgroup$
  • $\begingroup$ Can you explain the relationa after AF=f-a=f-c+g? It's not clear at all. $\endgroup$ – user146371 Jun 16 '14 at 14:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.